Interrelations between Pain and Alcohol: An Integrative Review - Zale, Emily L. (Clin Psychol Rev, 2015)
Pain and alcohol use are both highly prevalent in the general population, and pain-alcohol interrelations are of increasing empirical interest. Previous research has identified associations between pain and alcohol dependence, and the current review provides novel contributions to this emerging domain by incorporating studies that have tested relations between pain and low-to-moderate alcohol consumption, and by identifying potential psychosocial mechanisms of action. Specifically, we sought to integrate evidence of pain-alcohol relations derived from two directions of empirical inquiry (i.e., effects of alcohol on pain and effects of pain on alcohol use) across psychological, social, and biological literatures. We observed converging evidence that associations between alcohol consumption and pain may be curvilinear in nature. Whereas moderate alcohol use was observed to be associated with positive pain-related outcomes (e.g., greater quality of life), excessive drinking and alcohol use disorder appear to be associated with deleterious pain-related outcomes (e.g., greater pain severity). We also observed evidence that alcohol administration confers acute pain-inhibitory effects, and that situational pain may motivate alcohol consumption (e.g., drinking for pain-coping). Future research can inform theoretical and clinical applications through examination of temporal relations between pain and alcohol consumption, tests of hypothesized mechanisms, and the development of novel interventions.